(untitled) (Razão e Fé, 2021)
This paper seeks to problematize the process of formulating of the categorical imperative in Kant and Husserl. In the first part, the Kant’s conception is reconstructed from the beginning of the Groundwork of the Metaphysics of Morals until the exposition of the first formula of the categorical imperative. Along this path, some concepts dear to Kant’s argument are being clarified and problematized, such as, for example, the concepts of good will and duty. In the second part, the work seeks to show the origin of the formulation of the husserlian categorical imperative, as well as to understand the role of this imperative in the ethical conception of this author. In the final considerations, the intent of the work is to highlight the peculiarities pertinent to each proposal and to verify the possibility of a intersection.